A distinct molecular mechanism by which phenytoin rescues a novel long QT 3 variant. (July 2020) - Gando, Ivan; Campana, Chiara; Tan, Reina Bianca; Cecchin, Frank; Sobie, Eric A.; Coetzee, William A.
Abstract: Background: Genetic variants in SCN5A can result in channelopathies such as the long QT syndrome type 3 (LQT3), but the therapeutic response to Na + channel blockers can vary. We previously reported a case of an infant with malignant LQT3 and a missense Q1475P SCN5A variant, who was effectively treated with phenytoin, but only partially with mexiletine. Here, we functionally characterized this variant and investigated possible mechanisms for the differential drug actions. Methods: Wild-type or mutant Nav 1.5 cDNAs were examined in transfected HEK293 cells with patch clamping and biochemical assays. We used computational modeling to provide insights into altered channel kinetics and to predict effects on the action potential. Results: The Q1475P variant in Nav 1.5 reduced the current density and channel surface expression, characteristic of a trafficking defect. The variant also led to positive shifts in the voltage dependence of steady-state activation and inactivation, faster inactivation and recovery from inactivation, and increased the "late" Na + current. Simulations of Nav 1.5 gating with a 9-state Markov model suggested that transitions from inactivated to closed states were accelerated in Q1475P channels, leading to accumulation of channels in non-inactivated closed states. Simulations with a human ventricular myocyte model predicted action potential prolongation with Q1475P, compared with wild type, channels. Patch clamp data showed that mexiletine and phenytoin similarly rescued some of the gating defects. Chronic incubation with mexiletine, but not phenytoin, rescued the Nav 1.5-Q1475P trafficking defect, thus increasing mutant channel expression. Conclusions: The gain-of-function effects of Nav 1.5-Q1475P predominate to cause a malignant long QT phenotype. Phenytoin partially corrects the gating defect without restoring surface expression of the mutant channel, whereas mexiletine restores surface expression of the mutant channel, which may explain the lack of efficacy of mexiletine when compared to phenytoin. Our data makes a case for experimental studies before embarking on a one-for-all therapy of arrhythmias. Graphical abstract: Unlabelled Image Highlights: Arrhythmias in child with Nav1.5-Q1475P was better controlled by phenytoin but not mexilitine. Nav1.5-Q1475P had gain-of-function (e.g. increased late current) and trafficking defects. Numerical modeling shows the channel is trapped in a pre-open closed state with a longer APD. Mexiltine, but not phenytoin, rescued trafficking of the mutant channel. Phenytoin may be better since it partially rescues gating, but not trafficking defects.